Building a validity argument for the Test of English as a Foreign Language - Chapelle, Carol A.; Enright, Mary; Jamieson, Joan (ESL & applied linguistics professional series., 2008)
The Test of English as a Foreign Language (TOEFL[registered]) is used by several universities to guide English language instruction. This volume provides a detailed description and analysis of Educational Testing Service's research and development efforts to develop a major revision of the TOEFL[registered] test.